2008
DOI: 10.1175/2007jcli1908.1
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Trend of North West Australia Rainfall: Observations and Coupled Climate Modeling

Abstract: Since 1950, there has been an increase in rainfall over North West Australia (NWA), occurring mainly during the Southern Hemisphere (SH) summer season. A recent study using 20 th century multi-member ensemble simulations in a global climate model forced with and without increasing anthropogenic aerosols suggests that the rainfall increase is attributable to increasing Northern Hemisphere aerosols. The present study investigates the dynamics of the observed trend toward increased rainfall and compares the obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
82
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 36 publications
6
82
2
Order By: Relevance
“…The rainfall decrease in SWWA has been studied intensely in recent years (e.g. Smith et al, 2000;Cai and Watterson, 2002;IOCI, 2002;Pitman et al, 2004;Cai et al, 2005;Cai and Cowan, 2006;Hope et al, 2006;Meneghini et al, 2007;Feng et al, 2010aFeng et al, , 2010b, as has the increasing trend in NWA (Wardle and Smith, 2004;Rotstayn et al, 2006;Shi et al, 2008aShi et al, , 2008bTaschetto and England, 2008). In contrast, relatively little is known of the cause and mechanism of the decreased NEA rainfall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rainfall decrease in SWWA has been studied intensely in recent years (e.g. Smith et al, 2000;Cai and Watterson, 2002;IOCI, 2002;Pitman et al, 2004;Cai et al, 2005;Cai and Cowan, 2006;Hope et al, 2006;Meneghini et al, 2007;Feng et al, 2010aFeng et al, , 2010b, as has the increasing trend in NWA (Wardle and Smith, 2004;Rotstayn et al, 2006;Shi et al, 2008aShi et al, , 2008bTaschetto and England, 2008). In contrast, relatively little is known of the cause and mechanism of the decreased NEA rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al (2008a) reported an anomalously high sea level pressure (SLP) over much of the Australian continent; the anticyclone circulation pattern is associated with southeasterly flows in NEA, resulting in variable rainfall east of 130°E and anomalously low rainfall to the west. However, the Australian anticyclone is located over southern Australia (south of 25°S) in austral summer; the region north of 25°S in Australia is strongly influenced by easterlies.…”
Section: Introductionmentioning
confidence: 99%
“…Another uncertainty concerns the simulation of ENSO itself in the model. In common with most other GCMs, Mk3.6 suffers from the Pacific equatorial cold-tongue bias: the tongue of SST anomalies associated with ENSO extends too far west towards the eastern Indian Ocean, which is expected to generate an ENSO-rainfall relationship that is centred too far west over Australia (e.g., Shi et al, 2008). How this relates to our results should be considered in a future study.…”
Section: Discussionmentioning
confidence: 60%
“…Shi et al, 2008;Brown, Jakob, and Haynes 2010;Kirono and Kent 2011;Cai et al, 2011;Colman, Moise, and Hanson 2011;Jourdain et al, 2013). Differences between simulated and observed trends in rainfall have been noted in Räisänen (2007) and Kirono and Kent (2011).…”
Section: Discussionmentioning
confidence: 93%